Performance Analysis of AlxGa1-xAs/epi-Si(Ge) Tandem Solar Cells: A Simulation Study. (December 2015) - Lachaume, R.; Cariou, R.; Decobert, J.; Foldyna, M.; Hamon, G.; Cabarrocas, P. Roca i; Alvarez, J.; Kleider, J.-P.
Abstract: A new strategy for the development of III-V/Si tandem solar cells has recently been proposed consisting in low temperature PECVD epitaxy of silicon or silicon-germanium on gallium-arsenide. This paper thus gives first insights about theoretical but realistic maximum performance of such tandem cells by means of full numerical simulations considering perfect layers and interfaces. The consequences of using a thin epi-Si bottom cell instead of a thick silicon substrate are investigated. In case no light trapping scheme is considered, a minimum epi-layer thickness of 20 μm is mandatory for the tandem to exhibit higher conversion efficiencies than a single GaAs solar cell. The epi-Si can yet be advantageously replaced by an epitaxial silicon-germanium alloy to increase the bottom cell optical absorption and thus decrease the minimum required thickness by a factor of ∼4 (∼5 μm). Finally, simulations show that over 33% efficiency can be obtained for Alx Ga1-x As/epi-Si0.63 Ge0.27, which confirms that this is a promising new concept.